Trichoderma erinaceum Bio-Priming Modulates the WRKYs Defense Programming in Tomato Against the Fusarium oxysporum f. sp. lycopersici (Fol) Challenged Condition - Aamir, Mohd; Kashyap, Sarvesh Pratap; Zehra, Andleeb; Dubey, Manish Kumar; Singh, Vinay Kumar; Ansari, Waquar Akhtar; Upadhyay, Ram S.; Singh, Surendra (Frontiers in Plant Science, 2019)
The beneficial association and interaction of rhizocompetent microorganism are widely used for plant biofertilization and amelioration of stress-induced damages in plants. To explore the regulatory mechanism involved in plant defense while associating with beneficial microbial species, and their interplay when co-inoculated with pathogen, we evaluated the response of tomato defense-related WRKY gene transcripts. The present study was carried out to examine the qRT–PCR-based relative quantification of differently expressed defence-related genes in tomato (Solanum lycopersicum L.; variety S-22) primed with Trichoderma erinaceum against the vascular wilt pathogen (Fusarium oxysporum f. sp.lycopersici). The tissue specific and time bound expression profile changes revealed highest upregulation was observed in transcript profile of SlWRKY31(root) and SlWRKY37(leaf) in T. erinaceum bioprimed treated plants at 24 hrs with 16.51- and 14.07- fold increase respectively. In contrast, SlWRKY4 showed downregulation with highest repression in T.erinaceum bioprimed root (24 hrs) and leaf (48 hrs) tissue samples with 0.03 and 0.08 fold decrease respectively. Qualitative expression of PR proteins (chitinases and glucanases) was found elicited in T.erinaceum primed plants. However, the antioxidative activity of tomato Superoxide dismutase and catalase increased with highest upregulation of SOD and GPX1 in Fol+ T.erinaceum treatments. We observed that these expression changes were accompanied by 32.06% lesser H2O2 production in T. erinaceum bioprimed samples. The aggravated defense response in all the treated conditions was also reflected by an increased lignified tissue. Overall, we conclude that T. erinaceum biopriming modulated the defense transcriptome of tomato following the Fol challenged conditions, and were accompanied by enhanced accumulation of defense-related WRKY transcripts, increased antioxidative enzyme activities and the reinforcements through a higher number of lignified cell layers.